PARENTS’ OPINION REGARDING THE USE OF DISTANCE LEARNING DURING COVID-19 PANDEMIC - MARIN, Diana-Crina; BOCOȘ, Mușata; CĂLIN, Cecilia-Veronica; CORDOȘ, Ildiko (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2020)
Through this research paper, we aimed at studying the conditions in which distance learning processes have taken place at primary school level, during the temporal suspension of the face-to-face courses in pre-university education from Romania. We have also proposed some recommendations for decision-makers, educational researchers, and primary school practitioners. The questionnaire was applied in the online environment, between March 29ᵗʰ - May 5ᵗʰ of 2020. The sample of participants consisted of 1456 parents of primary school students. The results of the study revealed that some of the students faced various technical difficulties or emotional problems, and for some pupils, the level of motivation for learning decreased. Also, from the perspective of the parents, coherent and effective health education programs need to be implemented in schools, now or immediately after the end of this pandemic.